The Character-Based Parenting Patterns in Ulul Ilmi's Girls' Dormitory: Improving Students' Mental Health and Achieving Quality Education - Nurti Budiyanti; Kokom Siti Komariah; Indah Sari; Jenuri Jenuri (Bulletin of Pedagogical Research, 2025)
This article examines the implementation of Ulul Ilmi character-based parenting in female dormitories as a strategy to enhance students’ mental health and educational attainment. The Ulul Ilmi concept, which integrates scientific knowledge with Islamic values, is designed to foster positive character development among students, thereby supporting both their psychological well-being and academic success. Employing a qualitative case study approach in the Universitas Pendidikan Indonesia (UPI) dormitory, data were collected through in-depth interviews, observations, and documentation analysis. The findings reveal that Ulul Ilmi character-based parenting creates a supportive environment that strengthens students’ emotional resilience, mental health, and learning motivation, ultimately improving academic achievement. Furthermore, the study highlights the role of spiritual and social reinforcement in shaping constructive peer interactions and promoting holistic self-development. This study contributes to the growing discourse on character education and mental health in higher education by offering an integrative model of parenting in dormitory settings. It demonstrates that embedding Ulul Ilmi values into parenting practices not only enhances students’ well-being but also provides a framework for fostering a healthier, value-driven academic environment. These insights can inform dormitory management policies and character-based education programs in both national and international contexts.